2007
DOI: 10.1038/sj.npp.1301600
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Phenethylamine Hallucinogen Treatment Alters Behavioral Sensitivity to a Metabotropic Glutamate 2/3 Receptor Agonist

Abstract: Recent clinical studies in schizophrenic patients show that a selective agonist of group II metabotropic glutamate (mGlu) receptors has robust efficacy in treating positive and negative symptoms. Group II mGlu receptor agonists also modulate the in vivo activity of psychotomimetic drugs, reducing the ability of psychotomimetic hallucinogens to increase glutamatergic transmission. The use of mouse models provides an opportunity to investigate the dynamic action that mGlu2/3 receptors play in regulating the beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Both 5-HT 2A and mGlu2 receptors have been implicated in schizophrenia (Roth et al 1998;Benneyworth et al 2007Benneyworth et al , 2008. Activation of mGlu2 receptor increases affinity of 5-HT 2A receptors, whereas activation of 5-HT 2A receptors decreases mGlu2 receptor affinity.…”
Section: Membrane Proteinsmentioning
confidence: 99%
“…Both 5-HT 2A and mGlu2 receptors have been implicated in schizophrenia (Roth et al 1998;Benneyworth et al 2007Benneyworth et al , 2008. Activation of mGlu2 receptor increases affinity of 5-HT 2A receptors, whereas activation of 5-HT 2A receptors decreases mGlu2 receptor affinity.…”
Section: Membrane Proteinsmentioning
confidence: 99%
“…On the other hand, the locomotor activity induced by the mGlu 2/3 R antagonist LY341495 is attenuated in 5-HT 2A -KO mice [74]. Moreover, chronic administration of the hallucinogenic 5-HT 2A agonist 2,5-Dimethoxy-4-bromoamphetamine (DOB) in mice attenuates the behavioral effects of the mGlu 2/3 R agonist LY379268 [95] whereas chronic treatment by LY341495 decreases 5-HT 2A binding and the hallucinogenic effects of LSD [96]. …”
Section: Mglu2r and Schizophreniamentioning
confidence: 99%
“…heterodimers or oligomers [135,[146][147][148][149][150][151][152][153][154]. Several laboratories have shown that metabotropic glutamate receptor 2/3 (mGluR2/3) activation is able to affect the cellular [155][156][157], electrophysiological [78,117,158,159] and behavioral [155,[160][161][162][163][164] responses induced by 5-HT2AR. It has been recently reported that 5-HT2AR forms a receptor complex with mGluR2 [56].…”
Section: Cellular Responses Induced By Hallucinogenic Drugsmentioning
confidence: 99%